RANCANG BANGUN AUGMENTED REALITY WISATA DERMAGA KERENG BANGKIRAI BERBASIS MOBILE: Mobile-Based Augmented Reality Design For Kereng Bangkirai Pier Tourism - Pebriansen, Yairus; Haryadi, Haryadi; Windiarti, Ika Safitri (Jurnal Sains Komputer dan Teknologi Informasi, 2024)
The promotion of Kereng Bangkirai Pier Tourism is still limited to a web that displays photos of objects in the tourist area. Therefore, it is necessary to carry out more interesting promotions by utilizing Augmented Reality technology, because this technology is able to combine 2D or 3D virtual objects into the real environment, creating a mixed space (mixed reality) in real time. This research aims to develop a mobile-based Augmented Reality for Kereng Bangkirai Pier Tourism. This AR application is also expected to help in marketing and promoting tourism at Kereng Bangkirai Pier, providing more informative and interesting information to visitors. This study uses an observation method to collect the necessary information. As for application development, the SDLC method is used, which is then implemented with the Unity editor with the Vuforia SDK. The application can be installed and operates properly on Android version 8.0 – 8.1 (Oreo) and above and the resolution is above 5mp. In this application, the main menu and display are displayed in the form of Pier Tourism Icons, ecotourism natural tourism displays, types of natural tourism, educational tours, general information on the pier, culinary tours, application instructions and about the application. Based on the results obtained from the questionnaire, this application is very feasible to use.